Hierarchical Analysis of Foodstuffs and Housing in the Formation of the Final CPI After the Covid Pandemic -19 Early 2019-2021 in Ternate City - Bakri Soamole; Mohammad Kotib; Firdaus Duko (Journal of Social Research, 2024)
The review of the study on Edibles and Ownership of very expensive housing will be felt with the continuous high increase in general prices which results in the price of goods that are increasingly scarce in the market, these expensive all the imbalance of demand and supply does not become constant. The economy is currently spinning during the covid-19 pandemic, Social Limitations are the main cause while on the other hand, health is very important when hit by the covid-19 attack. All economic and health joints become sook (stagnant) in the sense that everyone needs rest. However, everyone also needs food, so everyone needs a job to earn income which leads to social welfare, food and board. The city of Ternate is Ternate is currently facing the challenges of high food staple prices and a strong demand for housing, which have made market conditions increasingly unstable. This situation necessitates balanced, measurable policies from all stakeholders in both the short and medium term to stabilize staple food prices. The city also grapples with complex issues such as high transportation costs and long distribution lines, all of which demand effective solutions to control prices and ensure market stability.